ANALISIS RISIKO PRODUKSI DAN RISIKO PENDAPATAN PADA USAHATANI PADI DI KECAMATAN BAURENO KABUPATEN BOJONEGORO - Sri Sari Utami; Widhi Netraning Pertiwi (JURNAL VIGOR, 2021)
Rice is one of the leading commodities for Baureno District, Bojonegoro Regency. Along with high revenue potential, farmers working in this area also have to face various agricultural risks. This study aims to analyze the production risk and income risk of rice farming. The study was conducted in Baureno District, Bojonegoro Regency, involving 55 farmers as respondents who were selected by simple random sampling. The level of production risk and farm income is calculated by the coefficient of variation analysis. The results of this study showed that rice farming in Baureno sub-district has high production risk and income risk, as indicated by the analysis of the coefficient of variation on production risk of 0.584 and income risk of 0.626.Keywords: Production risk, income, rice